Theoretical Study of Phosphoethanolamine: A Synthetic Anticancer Agent with Broad Antitumor Activity - Vitor Prates Lorenzo; Francisco Jaime Bezerra Mendonça Júnior; José Maria Barbosa Filho; Luciana Scotti; Marcus Tullius Scotti (Journal of Chemistry)
Cancer is a major public health problem with limited success of available treatments, pointing to the need for new strategies to be developed. Phosphoethanolamine exhibits broad antitumor activity in a variety of tumor cells and potent inhibitor effects on tumor progress in vivo. Once-used organophosphates inhibit acetylcholinesterase (AChE), resulting in toxic effects to the user. As this group is present in phosphoethanolamine, we perform prediction of the in silico metabolism of phosphoethanolamine and submit this series to a docking study on AChE. A total of 10 metabolites were indicated by the prediction, including ammonia and hydroxylamine, which were not included in the study. Using a group of 8 organophosphorus whose pIC50 values ranged from 5.92 to 9.47 as template, we observed that no compound present in the phosphoethanolamine series had a binding energy lower than that of organophosphorus, suggesting that the series has low inhibitory power on AChE. In light of this, we conclude that phosphoethanolamine and its predicted metabolites do not significantly inhibit AChE to cause a cholinergic crisis. This finding highlights the importance of investigating this compound as lead for potential anticancer agents.